2011
DOI: 10.1002/lary.21404
|View full text |Cite
|
Sign up to set email alerts
|

Correlative study of indirect computed tomography lymphography using iopamidol and histopathology in a cervical lymph node metastasis model

Abstract: Indirect CT-LG may be useful for differentiating metastatic from nonmetastatic lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Therefore, the deep cervical lymph nodes were confirmed to be the SLNs of tongue by dynamic observation of draining of Gd-Au PENPs to the SLNs and by indirect lymphography, which was consistent with previous findings [21,23,27]. …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, the deep cervical lymph nodes were confirmed to be the SLNs of tongue by dynamic observation of draining of Gd-Au PENPs to the SLNs and by indirect lymphography, which was consistent with previous findings [21,23,27]. …”
Section: Discussionsupporting
confidence: 79%
“…One of the reasons for a few clinical application of SLN identification by indirect lymphography with clinically used iodine and gadolinium-containing contrast agents is that these traditional small molecular contrast agents could easily wash in and out of the SLN, resulting in a short duration of enhancement imaging, which does not benefit SLN detection in the deep viscera, such as the larynx and laryngopharynx. In our previous studies of a tongue VX 2 carcinoma model, the enhancement peak was observed 1 min after contrast injection, ranging from 600 to 800 HU, and the duration of high intensity of SLN enhancement lasted only for 3-5 min, then the intensity of SLN enhancement decreased dramatically due to rapid washout of the agent from the lymph node, and declined to normal (<80 HU) 15 min after contrast injection [21,23]. The short duration of SLN enhancement due to rapid washout of the traditional contrast agents increased the difficulty of SLN detection because of low contrast agent concentration in the SLNs, and its clinical application was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic variability is documented in both people and dogs . The medial iliac lymph node was most commonly identified as a sentinel lymph node for anal sac gland carcinoma in our study (eight of 15 lymph nodes, 53%), followed by the sacral lymph node (5/15, 33%) and the internal iliac lymph node (2/15, 13%).…”
Section: Discussionmentioning
confidence: 95%
“…However, gold‐standard methods of sentinel lymph node mapping used in people, such as lymphoscintigraphy, are not widely available to veterinarians. Indirect computed tomographic lymphography has been used successfully in both people and experimental animals for lymphatic and sentinel lymph node mapping . As CT capability has become more readily available to veterinarians, the objective of this study was to evaluate the feasibility of an indirect CT lymphography technique as a possible method for sentinel lymph node identification in a complex lymphocenter using a natural model of disease prone to lymphatic metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation